The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41467-020-16816-2
|View full text |Cite|
|
Sign up to set email alerts
|

A dietary fatty acid counteracts neuronal mechanical sensitization

Abstract: PIEZO2 is the essential transduction channel for touch discrimination, vibration, and proprioception. Mice and humans lacking Piezo2 experience severe mechanosensory and proprioceptive deficits and fail to develop tactile allodynia. Bradykinin, a proalgesic agent released during inflammation, potentiates PIEZO2 activity. Molecules that decrease PIEZO2 function could reduce heightened touch responses during inflammation. Here, we find that the dietary fatty acid margaric acid (MA) decreases PIEZO2 function in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 60 publications
2
67
0
Order By: Relevance
“…To test this hypothesis, we examined the effect of the actin cytoskeleton-disrupting drug Cytochalasin-D on PIEZO2 and IDR5 del -mediated currents. As previously shown for PIEZO1 35,40,47 and PIEZO2 39,48 , treatment with Cytochalasin-D (15 min, 1 µM) significantly reduced membrane indentation-evoked current amplitudes of full-length PIEZO2 ( Fig. 5a and b) without affecting the mechanical activation threshold and inactivation kinetics ( Fig.…”
Section: Idr5 Is Required For Force-from-filament Gating Of Piezo2supporting
confidence: 82%
“…To test this hypothesis, we examined the effect of the actin cytoskeleton-disrupting drug Cytochalasin-D on PIEZO2 and IDR5 del -mediated currents. As previously shown for PIEZO1 35,40,47 and PIEZO2 39,48 , treatment with Cytochalasin-D (15 min, 1 µM) significantly reduced membrane indentation-evoked current amplitudes of full-length PIEZO2 ( Fig. 5a and b) without affecting the mechanical activation threshold and inactivation kinetics ( Fig.…”
Section: Idr5 Is Required For Force-from-filament Gating Of Piezo2supporting
confidence: 82%
“…1D-F) indicating that the responses in the TACAN transfected group were unlikely to be due to the lack of TACAN expression, and the lack of responses were not due to the lack of Piezo2. To ensure that the reduction in Piezo2 channel activity is not specific to HEK293 cells, we also co-expressed TACAN with Piezo2 in Neuro2A (N2A) cells in which Piezo1 was deleted with CRISPR (Moroni et al, 2018;Romero et al, 2020). In these cells we could perform deeper indentations of the cell without losing the seal, thus we detected larger currents.…”
Section: Resultsmentioning
confidence: 99%
“…Recent preprints showed that the structure of TACAN determined by cryoEM showed similarity to the fatty acid elongase ELOVL, and the structure of TACAN also contained a coenzyme-A molecule (Niu et al, 2021; Rong et al, 2021; Xue et al, 2021). Piezo2 as well as Piezo1 were shown to be regulated by a variety of lipids (Borbiro et al, 2015; Narayanan et al, 2018; Romero et al, 2020; Romero et al, 2019), therefore it is possible that TACAN modulates Piezo2 activity through modifying the lipid content of the cell. Exploring this possibility will be a subject of future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Piezo2 is an essential mechanotransduction channel for the sensation of touch, proprioception, tactile allodynia, and mechanical pain in various kinds of neurons. 41,[149][150][151] Conditional deletion of Piezo2 in CNS neurons decreased the sensitivity to gentle dynamic touch without affecting the sensitivity to noxious pinch. 149 Dorsal root ganglia (DRG) sensory neurons mediate distinct sensations of touch, proprioception, and mechanical pain.…”
Section: Piezo Proteins In Other Cells and Tissuesmentioning
confidence: 99%